The MAP-Hand: Psychometric properties and differences in activity performance between patients with carpometacarpal osteoarthritis and rheumatoid arthritis - Anne Therese Tveter; Nina Østerås; Randi Nossum; Ruth Else Eide; Åse Klokkeide; Karin Hoegh Matre; Monika Olsen; Øyvor Andreassen; Alison Hammond; Ingvild Kjeken (Medical Journals Sweden, 2020)
Objective: To assess construct validity (Rasch analyses) of the Measure of Activity Performance of the Hand (MAP-Hand) in people with carpometacarpal osteoarthritis (CMC1 OA), and to explore differences in activity performance between people with CMC1 OA and those with rheumatoid arthritis. Design: Cross-sectional study. Subjects: A total of 180 people with CMC1 OA referred for surgical consultation were recruited from rheumatology clinics in Norway, and 340 people with rheumatoid arthritis were recruited from outpatient rheumatology clinics in the UK. Methods: The MAP-Hand consists of 18 predefined items scored on a 4-point scale from 1 (no difficulty) to 4 (unable to do), from which a mean score is calculated. Construct validity was assessed using Rasch analyses. Differences between the 2 groups were assessed using an independent sample t-test at the group level and differential item functioning (condition as grouping variable) at the item level. Results: Some mis-targeting of data and clusters of dependency were found, but the MAP-Hand scores showed an overall fit to the model. No between-group difference in total mean MAP-Hand score was found, but there were significant differences between the 2 groups on item levels. Conclusion: The MAP-Hand showed satisfactory construct validity and could differentiate between people with CMC1 OA and those with rheumatoid arthritis on item levels.